Penerapan Manajemen Pemasaran Berbasis Online dan Pengemasan / Pelabelan Pada Usaha UMKM Posdaya Soka - Dewi Kurniawati; Supriadi Thalib; Harimurti Wulandjani; Setiarini (FEB-UP Press, 2021)
Posdaya Soka having its address at Jatayu Raya Kampung Duku, Jalan Al-Barakah, RW 12, Kebayoran Lama Selatan Village, Kebayoran Lama District, South Jakarta, is part of the Community Empowerment Program by the Damandari Foundation in the Tabur Puja (Savings Pundi Sejahtera) program in 2012. Posdaya Soka was formed to raise the standard of living of the people in RW 12 Kebayoran Lama Selatan, South Jakarta. Posdaya Soka have weaknesses related to packaging/labeling and online marketing in the conditions of the covid 19 pandemic. The Team from FEB University Pancasila carried out the service to provide material and training on packaging/labeling and online marketing. Keywords: Posdaya Soka, packaging/labeling, online marketing